Analysis of the Causes of Investment Weakness in Kertajati Aerocity Business District - Pandora, Olivia; Rarasati, Ayomi Dita (Journal La Multiapp, 2025)
This study investigates physical issues and proposed improvement solutions in the development of the business district in Kertajati Aerocity. A mixed-method approach was aplied, combining qualitative descriptive statistics with the quantitative Analytical Hierarchy Process (AHP). The findings reveal two key physical issues contributing to the investment weakness in the Kertajati Aerocity Business District: accessibility and public facilities. Among these, issues related to public facilities were identified as having a higher priority (eigenvalue 0.595) compared to accessibility issues (eigenvalue 0.405). The public facilities problem specifically refers to the absence of entertainment facilities in the business district. Meanwhile, the accessibility issue pertains to limited road network provision. Proposed solutions to address the lack of entertainment facilities include the construction of entertainment infrastructure and partnerships or collaborations with investors. For the accessibility issue, suggested improvements involve building new road networks, prioritizing road development, and fostering collaborative investment schemes.